Long-term efficacy of electroconvulsive therapy combined with different antipsychotic drugs in previously resistant shizophrenia - Ravanić, Dragan (Array, 2009)
In treatment-resistant schizophrenia a combination of ECT with antipsychotics has been reported to have superior outcomes compared to other strategies, however the results were inconsistent. We investigated the long-term effects of the combination of unilateral, non-dominant hemisphere ECT with three antipsychotics. The clinical study was a naturalistic, prospective, openlabeled, active-controlled study in adult outpatients of both genders suffering from treatment-resistant schizophrenia with a follow up of 2 years. According to the results, the most effective treatment mode was olanzapine plus ECT, then risperidone plus ECT, while sulpiride plus ECT had lower clinical efficacy. The combination of novel antipsychotics and ECT can be used safely and effectively